Repeat Fig. 4 original dataset for Bacteria loaded with glucose polymer and photosensitive ICG silicon-nanoparticles for glioblastoma photothermal immunotherapy - Rong Sun (532754) (2025)
Bacteria can bypass the blood-brain barrier (BBB), suggesting the possibility of employment of bacteria for combating central nervous system diseases. Herein, we develop a bacteria-based drug delivery system for glioblastoma (GBM) photothermal immunotherapy. The system, which we name as ‘Trojan bacteria’, consists of bacteria loaded with glucose polymer and photosensitive ICG silicon-nanoparticles. In an orthotopic GBM mouse model, we demonstrate that the intravenously injected bacteria bypass the BBB, targeting and penetrating GBM tissues. Upon 808 nm-laser irradiation, the photothermal effects produced by ICG allow the destruction of bacterial cells and the adjacent tumour cells. Furthermore, the bacterial debris as well as the tumour-associated antigens promote antitumor immune responses that prolong the survival of GBM-bearing mice. Moreover, we demonstrate the residual bacteria are effectively eliminated from the body, supporting the potential therapeutic use of this system.